Genetic structure and diversity of the seagrass Zostera marina along a steep environmental gradient, with implications for genetic monitoring - Ries, Stefanie R.; Faust, Ellika; Johannesson, Kerstin; Jonsson, Per R.; Moksnes, Per-Olav; Pereyra, Ricardo T.; Jahnke, Marlene (Frontiers in Climate, 2023)
Zostera marina (eelgrass) is a foundation species in coastal zones in the northern hemisphere. Eelgrass is declining across its distribution, a trend likely to accelerate under climate change. In Sweden, eelgrass is a species of particular concern in management and conservation. Here, we provide information on genetic variation, an important component for the potential persistence and adaptation of any species in a changing environment. In particular, the steep salinity gradient over which eelgrass is distributed along the Swedish coast (26 psu on the west coast to 5 psu on the east coast) calls for a better understanding of genetic diversity, connectivity, and potential for local adaptation. To assess genetic variation and population genetic structure, we genotyped individuals with 2,138 single nucleotide polymorphisms (SNPs) from 15 eelgrass meadows spanning the whole Swedish distribution. We found a geographic population genetic structure from west to east parallel to the salinity gradient and with a clear genetic break at the entrance to the Baltic Sea. Meadows along the low salinity east coast consisted of a few or only one clone. Eelgrass on the west coast had higher genotypic richness, higher genetic variation, and showed population differentiation on smaller geographic scales. With their low genetic variation, the east coast meadows are especially threatened amidst global changes. Lack of sexual reproduction and the capacity to generate new genotypes is an issue that needs to be seriously considered in management and conservation. In addition, the lack of sexual reproduction renders clonal eelgrass less likely to recover and recolonize after disturbance, and more challenging to restore. The here provided information on genetic clusters, clonality, and genetic variation can be included for prioritizing meadows for conservation and for identifying meadows for restoration purposes. Most importantly, genetic monitoring is urgently needed to assess temporal genetic changes of eelgrass along the Swedish coast and elsewhere facing climate change.